Determinants of health related quality of life among type 2 diabetic patients attending National University of Malaysia Medical Centre / Aqil Mohammad Daher - Mohammad Daher, Aqil (Institute of Graduate Studies, UiTM, 2014)
Diabetes Mellitus is notorious for its metabolic effect, acute and long term complications and impact on Quality of Life (QOL). Plethora of literature has documented the negative impact of DM on QOL. Currently, religion and spirituality constitute a topic of great importance to most of the world’s population where researchers have notably focused attention on the relationship between religion, spirituality and Quality of Life (QOL). However there is little, if none is known about the relationship of spirituality and diabetes-related QOL. The primary aim of this study was to determine factors affecting QOL among sample of patients with type 2 diabetes mellitus attending the medical centre of National University of Malaysia, Kuala Lumpur, Malaysia specifically in relation to spirituality. For this purpose we had to translate the English version of Spiritual Wellbeing Scale (SWBS) into Malay language as well as validate the Malay version of SWBS among Malaysian general population at Klang Valley and thence we proceeded to measure diabetes-related QOL among diabetic patients at the National University of Malaysia Teaching Hospital.